Phenotype and Genotype of a Cohort of Chinese Children with Early-Onset Protein-Losing Enteropathy - Ye, Ziqing; Huang, Ying; Wang, Yuhuan; Lu, Junping; Wu, Jie; Yu, Zhuowen (The Journal of pediatrics, 2019)
To examine the phenotypes and perform next-generation sequencing in children with early-onset protein-losing enteropathy. We performed a retrospective review of 27 children with early-onset protein-losing enteropathy. Patients were characterized on clinical, immunologic, and systemic involvements. Targeted gene panel sequencing and whole-exome sequencing were performed in 9 patients. In 27 patients (55.6% male), median age of disease onset was 173 days, and 59.3% had onset of disease before 1 year of age. Initial gastrointestinal symptoms included diarrhea (74.1%), vomiting (33.3%), and abdominal distention (48.1%). All patients had hypoalbuminemia, with an average serum albumin concentration of 20.2 ± 5.4 g/L. Hypogammaglobulinemia was identified in 72% of the patients. Upper endoscopy showed typical presentation of intestinal lymphangiectasia (n = 13). Patients frequently received intravenous albumin and immunoglobulin infusions as well as parenteral nutrition. Next-generation sequencing in 9 patients with available DNA showed 1 patient had compound heterozygous CCBE1 mutations and 2 had novel homozygous DGAT1 mutations. Monogenic diseases were identified in 3 of 9 patients who underwent genetic sequencing. Three subjects (11.1%) died, of whom 2 had homozygous DGAT1 mutations. No significant correlation was found between age of symptom onset, serum albumin, serum IgG, lymphocyte count, CD4+ cells, and mortality. Monogenic diseases may be observed in children with early-onset protein-losing enteropathy, and genetic evaluation with next-generation sequencing should be considered.